EFL teachers’ technological use: possibilities, routine and expectations of generation Z - Kateryna Fodor; Фодор Катерина; Fodor Katalin („RIK-U” Kft., 2018)
Abstract. Informational technologies, including computers, the Internet and electronic delivery systems such as radios, televisions, and projectors among others are still a source of fears for many teachers everywhere in the world despite the fact that computers became available to them in the early 1980s, as personal computers were not necessarily attached to a mainframe computer any longer, i.e. language teachers could use them for language teaching having a wide range of new possibilities [4; 7]. The role of training teachers to use informational technologies has been recognized for more than 2 decades [9], and many studies on the use of technology in education proved that technology rich environment influences the learning process unequivocally in a positive way. Furthermore, Blake [3] introduces a concept, according to which computers can serve as language tutors with little or no support from real instructors. However, ‘research in schools suggests that much technology-oriented instruction fails to achieve a good balance’ [13, p.30]. Furthermore, Beatty [2, p.72] points out that “teachers need to be concerned about investing time and money in unproven technology”.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: EFL teachers; information technology; generation Z